PENERAPAN PERMAINAN ENGKLEK DALAM MENGEMBANGKANMOTORIK KASAR ANAK USIA DINI DI TK ARHADAR - Angraeni, Reni; Kurnia, Seila Dwi (Institut Agama Islam Negeri Bone, 2022)
This thesis discusses the application of crank games in developing gross motor skills of early childhood in Arhadar Kindergarten, Palakka District, Bone Regency. The problem in this thesis is what is the role of crank play in early childhood in group B at Arhadar Kindergarten, and how are children's gross motor skills through crank play in early childhood in group B in Arhadar Kindergarten which aims to to find out the role of crank play in early childhood in group B at Arhadar Kindergarten, and to find out the gross motor skills of children through crank play in early childhood in group B at Arhadar Kindergarten.To facilitate this research, descriptive qualitative research was used using pedagogic and psychological approaches. Data collection techniques used are observation, interview, and documentation techniques. The data obtained was analyzed in three stages, namely data reduction, data presentation, and drawing conclusions.The results of this study indicate that developing gross motor skills in early childhood through crank games is very effective. The teacher gives the opportunity for children to play the crank game. In addition, the teacher also gave directions on how to play the crank game. From this study, it can be concluded that in developing gross motor skills of children in Arhadar Kindergarten, crank games are very effective, and the impact of crank games is very large in developing gross motor skills in early childhood.